An exploratory study on local furniture designers and manufacturer's concepts of space-saving furniture - Mendoza, Daryl Joseph C.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
Urbanization has been one of the reasons for the decrease in the available space in urbanized areas, in turn it has caused space to become a luxury for people living in these areas. This issue may be addressed through proper planning and designing done by fields like urban planning, architecture, and interior design. Furniture design, specifically, can contribute in addressing the issues on small spaces by producing space saving furniture pieces. However, the definition of space-saving furniture has not been clearly established and is interpreted differently - such as convertible, folding, modular, and stacking furniture. This study investigated the understanding of local furniture designers and manufacturers on the concept of space-saving furniture - particularly their knowledge and ideas, the relevance, and the forms that they associate to it. It also examined the alignment of their concepts of space-saving to their translations into furniture design. The study used both the grounded theory and cross-referencing to analyze the data from the interviews. Purposive and convenience sampling was utilized to focus the set of respondents for the study - ten practicing furniture designers and manufacturers from different companies were interviewed. Findings show that various definitions of space-saving furniture served as the basis of producers to guide their decision making in design. It was also observed that differences in the informants backgrounds influenced their perspective on space-saving furniture. The motivations for the need to design and develop space-saving furniture ideas were mostly influenced by target consumers - their need and wants which are both driven by the functions of space-saving, as well as by the advertising and marketing of space-saving to the consumer market. Moreover, the different forms considered to be space-saving encompass a variety of ideas from the informants.
Submitted June 2016
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Furniture design -- Philippines